Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Kredit Cepat Aman (KCA) Pada Kantor Pegadaian Cabang Oesapa - Devin Irvandy; Fransina W. Ballo; Novi Theresia Kiak (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
Quick and Safe Credit (KCA) is one of the superior service product facilities of PT Pegadaian, which is a loan based on the pawn law with easy, safe, and fast service procedures. Quick and Safe Credit (KCA) is intended to help customers and communities with the problem of investment funds and funds for working capital.This study aims to analyze the factors that influence customer/community demand for PT Pegadaian’s Quick and Safe Credit (KCA) facility. This research is a quantitative descriptive study conducted at PT Pegadaian Oesapa Branch Kupang City. Data were collected using literature study methods, questionnaires, and observations. The results showed that the level of customer income, number of customer family dependents, and level of customer education had a significant effect on the demand for Quick and Safe Credit (KCA) at the Oesapa Branch Pegadaian office. This means that the higher the customer's income, the greater the number of dependents of the customer's family, and the higher the customer's education level, the greater the demand for Quick and Safe Credit (KCA).